Effect of circFOXM1/miR-218-5p on the proliferation, apoptosis and migration of glioma cells: CircFOXM1/miR-218-5p in glioma - Deng, Renzhi; Chen, Jianying; Qin, Jianying; Wang, Lei; Zhu, Dandan; Sun, Xuyong (Cellular and Molecular Biology, 2024)
This study aimed to explore the influence of circFOXM1/miR-218-5p molecular axis in the proliferation, apoptosis and migration of glioma cells. The levels of circFOXM1 and miR-218-5p in glioma and adjacent tissues were tested by qRT-PCR. Cultured human glioma U251 cells were randomly split into groups: si-NC, si-circFOXM1, miR-NC, miR-218-5p, si-circFOXM1+anti-miR-NC, si-circFOXM1+anti-miR-218-5p. MTT method, plate clone formation, flow cytometry and Transwell experiments were utilized for detecting the proliferation, clone formation, apoptosis and migration of glioma cells. Dual-luciferase reporter experiment authenticated the targeted relation of circFOXM1 and miR-218-5p. Western blot tested the levels of E-cadherin and N-cadherin. CircFOXM1 was upregulated while miR-218-5p was low expressed in glioma tissues versus normal tissues. After circFOXM1 silence or miR-218-5p overexpression, miR-218-5p level was increased, and cell apoptosis rate and E-cadherin expression were enhancive, whereas cell proliferation, cell clone formation and migration abilities, and N-cadherin level were reduced. CircFOXM1 could affect miR-218-5 level by negative regulation. Furthermore, miR-218-5p silence could reverse the stimulative influence of si-circFOXM1 on apoptosis rate, and E-cadherin level, and the repressive effect on cell viability, cell number of colony formation and migration, and N-cadherin expression. Inhibition of circFOXM1 expression could block the proliferation, clone formation, and migration and induce apoptosis of glioma cells by upregulating miR-218-5p.